Reflections on an Unreflected Sphere - Archaeological Exhibitions and Nationalism - Lundström, Inga; Pilvesmaa, Marja-Leena (Current Swedish Archaeology, 1998)
There is an open nationalism, clearly stated through national symbols as well as through various rituals. However, there is also an underlying form of nationalism, operating on a structural level, so obvious that it becomes "invisible". This is not only true for the actions of people in general, but to a great cxtent also for the understanding of different normative institutions, not least the museums. Nationalism is included as a hidden facet in the communicating activities. This article sheds light on the role of archaeology in this context, with particular emphasis on archaeological exhibitions. At a closer look, it becomes obvious that one elementary aspect of the archaeological communicating activities is missing —the conscious reflection.